2005
DOI: 10.1007/s10689-004-7991-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic uptake in BRCA-mutation families is related to emotional and behavioral communication characteristics of index patients

Abstract: Uptake of predictive BRCA-mutation testing by first- and second-degree relatives is low. Emotional and behavioral factors of index patients are related to this uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 9 publications
3
65
2
Order By: Relevance
“…24 This is consistent with the little previous research that has been conducted, which suggests that relatives who decline/defer testing may do so because they are not yet ready to take a BRCA1/2 test, they do not yet have children whom they feel obliged to pursue testing for and/or because of their lesser concerns for their own health as they have not yet reached the age of greatest HBOC risk. 13,14,25 Such factors may lessen the perceived benefits of testing for self and others and consequently reduce interest in taking the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This is consistent with the little previous research that has been conducted, which suggests that relatives who decline/defer testing may do so because they are not yet ready to take a BRCA1/2 test, they do not yet have children whom they feel obliged to pursue testing for and/or because of their lesser concerns for their own health as they have not yet reached the age of greatest HBOC risk. 13,14,25 Such factors may lessen the perceived benefits of testing for self and others and consequently reduce interest in taking the test.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Genetic information can be very detailed and complicated, and misconceptions about inheritance and genetics abound in the public consciousness. 15 Information given to patients by clinicians will be assimilated with preexisting knowledge about genetics when being conveyed to family members.…”
Section: Introductionmentioning
confidence: 99%
“…15 This is less commonly documented in the literature and the outcome of communication is often defined by the number of at-risk family members that contact the genetic services. 9 The frequency of contact is estimated to be between 20 and 40%, 18,19 and whereas barriers and facilitators to communication are well documented, 20 -24 the reason at-risk family members do not contact the genetic services is largely unknown. Exploration of families' experiences may further illuminate the process of communicating genetic information and provide evidence-based information for health professionals involved in the provision of genetic services.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this family communication actually occurs has been questioned, because of a lack of relatives presenting to genetic services for care. 2 Previous research on how families communicate genetic information has demonstrated that first-degree relatives are most commonly informed in comparison with second-and third-degree relatives who are informed less frequently. [3][4][5][6][7] Communication is often undertaken by women 8 and may follow gender lines, especially for familial breast and ovarian cancer and for X-linked conditions.…”
mentioning
confidence: 99%